Clinical use of apexlocator in everyday edodontic treatment (Эндодонтия Today)
In the following clinical situations dismantled everyday cases, require the use of apex locator Proper pixi to determine the length of the root canal. This device has a compact size, can continuously work not only in a dry root canal, but in all environments (solutions of hypochlorite sodium EDTA, various solvents), which is especially important in endodontic retreatment, the need of which occurs in recent years, more and more